2022
DOI: 10.37745/ijliss.15/vol8no1pp.9-18
|View full text |Cite
|
Sign up to set email alerts
|

The library Environment, Seat and Noise Making: The Case of Jiangsu University Library

Abstract: A good environment plays a fundamental role in the learning process of an individual. As Jiangsu University celebrates the 20th anniversary of consolidation and the 119th anniversary of its establishment, this study investigates the influence of the library in the student's life, especially the influence of seats and the effect noise has on students in the library environment. This survey uses a quantitative method by adapting a survey questionnaire in a face-to-face approach for data collection. Most particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Zotoo et al (2022) investigated library Environment, Seat and Noise Making: The Case of Jiangsu University Library. The study revealed that the designated places around the staircase are not really comfortable as they prefer seating sometimes.…”
mentioning
confidence: 99%
“…Zotoo et al (2022) investigated library Environment, Seat and Noise Making: The Case of Jiangsu University Library. The study revealed that the designated places around the staircase are not really comfortable as they prefer seating sometimes.…”
mentioning
confidence: 99%
“…Berikut adalah data yang diatur dan dikodekan menggunakan lembar kerja Microsoft Excel, kemudian disimpan dalam format CSV untuk pengolahan dan analisis lebih lanjut menggunakan perangkat lunak statistik SPSS. Data ini berasal dari kuesioner yang diisi oleh 500 responden yang sering mengunjungi perpustakaan [27]. Pada tanggal 3 Agustus 2023, peneliti mengumpulkan sejumlah survei yang diisi oleh 8 guru dan 53 siswa dari Sekolah Bodhi Dharma mengenai pentingnya IoT dalam bidang pendidikan, terutama di bagian perpustakaan.…”
unclassified